Study Analysis Of Concepts In Managing Effective And Effective Education Financing Efficient In Islamic Educational Institutions - Ulil Azmi; Kasful Anwar US; As'ad Isma (International Journal of Education, Vocational and Social Science, 2023)
Internal factors in financing an educational institution can contribute significantly to quality such as, teacher welfare, teacher ability, s class facilities, textbooks. The four components are inside The RAPBS requires a priority scale in obtaining cost allocations. One way of thinking is related to financial management (financing) in educational institutions is creative and dynamic in harmony with needs and developments that occur in society and the environment education. The link in preparing the budget is that you have to apply the principle of a balanced budget, meaning that income and expenditure plans must be balanced so that there is no minus income budget. With a balanced budget, the life of educational institutions will be effective and efficient in terms of finance, so that the centralization of financial management needs to be focused on the treasurers of educational institutions, to facilitate financial accountability. Investment costs for educational institutions include costs for providing facilities and infrastructure as well as human resource development costs. Meanwhile, personal costs include all kinds of costs that must be incurred by school students, including tuition fees (tuition fees) and practicum fees, in order to be able to take part in regular and ongoing learning.